Studi Spasial Kejadian Malaria Serta Pengaruh Kepadatan Plasmodium sp. Terhadap Anemia Dan Trombositopniapada Penderita Malaria Di Kabupaten Kepulauan Talaud - Pitreyadi Johanis Jusuf Sadukh; Joy Victor Imanuel Sambuaga; Bongakaraeng Bongakaraeng (Jurnal Kesehatan Lingkungan, 2020)
Malaria affects almost all components of the blood, and thrombocytopenia is one of the haematological abnormalities encountered and has received much attention in the scientific literature. Plasmodium infection can cause abnormalities in the structure and function of platelets. This study aims to spatialize/map the spread of malaria events, locations and physical and chemical environmental conditions of breeding places of malaria vectors and analyze the effect of Plasmodium sp density on anaemia and thrombocytopenia in malaria sufferers in Talaud Islands Regency in 2018. The research sample was malaria sufferers in April. Until August, who came to check at the Community Health Center in Talaud Islands Regency to obtain data on Plasmodium sp density, anaemia and thrombocytopenia, then coordinate data on the homes of malaria sufferers and Anopheles sp habitat and the physical and chemical environmental conditions of Anopheles sp habitat that were surveyed using tools Global Positioning System (GPS) is processed using the help of Arcgis 9.3 program. To analyze the effect of plasmodium sp density on anaemia and thrombocytopenia using Chi-square test statistics. The results of the study The spread of malaria incidence and the distance of Anopheles sp habitat with malaria sufferers' homes in Talaud Islands Regency in 2018 were spelt out. Physical environmental conditions (temperature and humidity) and chemical environment (pH and salinity) in the habitat of Anopheles sp. in residential areas of malaria sufferers are Temperature 27.9 - 29.8 0c, humidity 70.5% - 80.4%, pH in the range 5.6 - 8.1 and salinity 0.04 - 1.35 ‰. The density of Plasmodium sp in 34 malaria sufferers consisted of 18 cases +, 10 cases ++, 5 cases +++ and 1 case ++++. Statistical test results have a relationship between Plasmodium sp density against anaemia and thrombocytopenia in malaria sufferers in Talaud Islands District in 2018.